(untitled) (East West Medical College Journal, 2025)
Background: Anal fissure is a linear tear in the distal anal canal with spasm of internal anal sphincter. Lateral internal sphincterotomy (LIS) is the surgical treatment of choice for chronic anal fissure (CAF). Recently anal advancement flap (AAF) combined with tailored LIS gained popularity as there is rapid healing and relief of pain. In this study, we tried to evaluate the early outcome of combined tailored LIS with AAF and LIS alone in terms of patient’s morbidity. Methods: It was a randomized controlled trial (RCT), carried out in the Department of surgery, SSMCMH, Dhaka over a period of 8 months from February 2018 to September 2018. 30 patients of CAF had been chosen purposively and randomized into 2 groups. Control group (A) had 15 patients who underwent LIS alone and Experimental group (B) had 15 patients who underwent combined tailored LIS with AAF. Patients were followed up 3 months after operation Results: Post-operative pain was more Group A 6.53 ± 0.64 compared to 4.87 ± 0.63 in Group B with a p value <0.001. Post-operative bleeding was observed in 8 (53.30%) patients in Group A whereas no patient in Group B, with a significant p value, p <0.001. Post-operative hospital stay was less in Group A, 1.00 ± 0.00 days and 7.47 ± 0.64 days in Group B where p value was also significant, p <0.001. Minor pattern of incontinence was more in Group A 4 (26.70%) in comparison with 0 (0.00%) in Group B, p=0.032 which was statistically significant. Duration of wound healing was more 35.7 ± 3.31 days in Group A and 7.36 ± 0.49 days in Group B with a significant p value, p <0.001. Conclusions: Combined tailored LIS with AAF appears to produce the rapid healing, improvement of post-operative pain & bleeding, reducing risk of minor pattern of incontinence with few complications. EWMCJ Vol. 13, No. 2, July 2025: 91-96